Thoracic Aorta Diameter Calculation by Artificial Intelligence Can Predict the Degree of Arterial Stiffness - Wang, Yaoling; Yang, Jinrong; Lu, Yichen; Fan, Wenliang; Bai, Lijuan; Nie, Zhuang; Wang, Ruiyun; Yu, Jie; Liu, Lihua; Liu, Yun; He, Linfeng; Wen, Kai; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract: Background: Arterial aging is characterized by decreased vascular function caused by arterial stiffness (AS), and vascular morphological changes, caused by arterial dilatation. We analyzed the relationship of pre-AS and AS, as assessed by Cardio ankle vascular index (CAVI),with arterial diameters (AD) at nine levels, from the aortic sinus to the abdominal aorta, as measured by artificial intelligence(AI) on non-enhanced chest computed tomography (CT) images. Methods: Overall, 801 patients who underwent both chest CT scan and arterial elasticity test were enrolled.Nine horizontal diameters of the thoracic aorta (from the aortic sinuses of Valsalva to the abdominal aorta at the celiac axis origin) were measured by AI using CT. Patients were divided into non-AS (M.CAVI<8), pre-AS(8 ≤M.CAVI<9), and AS (M.CAVI≥9)groups, where M.CAVI is the mean value of left and right CAVIs. We compared AD differences among groups, analyzed the correlation of age, ADs, and M.CAVI or the mean pressure-independent CAVI(M.CAVI0), Furthermore, we evaluated the risk predictors of and the diagnostic value of the nine ADs for pre-AS and AS. Results: The AD at mid descending aorta (MD) correlated strongest with CAVI (r=0.46, p <0.001) or M.CAVI0(r=0.42, p<0.001). M.CAVI was most affected by the MD AD and by age. An increase in the MD AD independently predicted the occurrence of pre-AS or AS. For MD AD, every 4.37-mm increase caused a 14% increase in the pre-AS and AS risk, and a 13% increase in the AS only risk. With a cut-off value of 26.95mm for MD AD, the area under the curve(AUC) for identifying the risk of AS was 0.743. With a cut-off value of 25.15mm, the AUC for identifying the risk of the stage after the prophase of AS is 0.739. Conclusions: Aging is associated with an increase in AD and a decrease in arterial elasticity. An increase in AD, particularly at MD level is an independent predictor of AS development.